Prognostic role of macrophages and mast cells in the microenvironment of hepatocellular carcinoma after resection - Ali, Esraa; Červenková, Lenka; Pálek, Richard; Ambrozkiewicz, Filip; Hošek, Petr; Daum, Ondrej; Liška, Václav; Hemminki, Kari; Trailin, Andriy (BMC cancer, 2024)
BACKGROUND: The prognostic significance of mast cells and different phenotypes of macrophages in the microenvironment of hepatocellular carcinoma (HCC) following resection is unclear. We aimed in this study to assess the local distribution of infiltrating macrophages and mast cells of specific phenotypes in tissues of HCC and to evaluate their prognostic values for survival of post-surgical patients. METHODS: The clinicopathological and follow-up data of 70 patients with HCC, who underwent curative resection of tumor from 1997 to 2019, were collected. The infiltration of CD68+ and CD163+ macrophages and CD117+ mast cells was assessed immunohistochemically in representative resected specimens of HCC and adjacent tissues. The area fraction (AF) of positively stained cells was estimated automatically using QuPath image analysis software in several regions, such as tumor center (TC), inner margin (IM), outer margin (OM), and peritumor (PT) area. The prognostic significance of immune cells, individually and in associations, for time to recurrence (TTR), disease-free survival (DFS), and overall survival (OS) was evaluated using Kaplan-Meier and Cox regression analyses. RESULTS: High AF of CD68+ macrophages in TC and IM and high AF of mast cells in IM and PT area were associated with a longer DFS. High AF of CD163+ macrophages in PT area correlated with a shorter DFS. Patients from CD163TChigh & CD68TClow group had a shorter DFS compared to all the rest of the groups, and cases with CD163IMlow & CD68IMhigh demonstrated significantly longer DFS compared to low AF of both markers. Patients from CD68IMhigh & CD163PTlow group, CD117IMhigh & CD163PTlow group, and CD117PThigh & CD163PTlow group had a significantly longer DFS compared to all other combinations of respective cells. CONCLUSIONS: The individual prognostic impact of CD68+ and CD163+ macrophages and mast cells in the microenvironment of HCC after resection depends on their abundance and location, whereas the cumulative impact is built upon combination of different cell phenotypes within and between regions.
Keywords: Liver Neoplasms; Tumor Microenvironment; nádorové mikroprostředí; Peritumor area; mastocyty; nádory jater; Prognosis; Kaplan-Meier Estimate; Kaplanův-Meierův odhad; Tumor-infiltrating macrophages; Hepatocellular carcinoma; Macrophages; prognóza; Humans; makrofágy; Mast Cells; Mast cells; Carcinoma, Hepatocellular; Disease-free survival; Inner margin; lidé; hepatocelulární karcinom